PENGARUH INFLUENCER REVIEW DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT BELI PRODUK TAS DI KALANGAN MAHASISWA KOTA SURABAYA - Wahyu, Wega Sri; Saino, Saino (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This research was conducted to determine the effect of Influencer Reviews and Online Customer Reviews on the intention to buy bag products among Surabaya City students. This research uses descriptive quantitative. The population in this study are students in the city of Surabaya. The sample used was a minimum of 100 samples and 115 samples were used for this study with the criteria of active students in the city of Surabaya aged 17-24 years, using a purposive sampling technique and using the Rao Purba formula. The data analysis technique used was multiple linear regression analysis in this study using the IBM version 25 SPSS program. The results of this study indicate that partially the Influencer Review variable (X1) has an effect on the intention to buy bags in the city of Surabaya and the Online Customer Review variable (X2) has an effect on the intention to buy bags in the city of Surabaya. As well as simultaneously Influencer Reviews and Online Customer Reviews (X2) jointly influence the intention to buy bags in the city of Surabaya. Keywords: Influencer Reviews, Online Customer Reviews, Purchase Intention.